The Nature of Humanity from the Perspective of Islamic Educational Philosophy - Ika Nur Aisyah; Mayangsari; Tiara Safitri; Riska Nadira; Miftahul Arifin (Penerbit Hellow Pustaka, 2025)
This article aims to explain the nature of humanity according to Islamic educational philosophy in order to provide a clear understanding of human nature. This research employs a qualitative approach, focusing on a literature study, relying primarily on journals, the internet, and other scientific articles. The collected data is analyzed using content analysis, which facilitates the authors in filtering out key ideas from various sources to be organized within the focus of the study. This research aims to provide a comprehensive understanding of human nature, which is crucial for educational development and achieving the expected goals.